2023
DOI: 10.1021/acs.iecr.3c01848
|View full text |Cite
|
Sign up to set email alerts
|

Novel CFD-DEM Model for Spouted Bed Drying Incorporating Intraparticle Heat and Mass Diffusion

Abstract: In the final phase of particle drying in a spouted bed, the drying rate is governed by intraparticle heat and mass diffusion. Coupled computational fluid dynamics and the discrete element method (CFD-DEM) have proven to be suitable tools for modeling gas–solid in a spouted bed. However, existing CFD-DEM models are primarily employed to calculate the interphase heat and mass transfer rates based on an assumption of uniform intraparticle temperature and moisture distributions. Alternatively, some models take in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Che et al demonstrated that during the final phase of particle drying in a spouted bed, intraparticle heat and mass diffusion primarily control the drying rate. They employed a coupled CFD and discrete element method (DEM) (CFD–DEM) to model the gas–solid interactions within a spouted bed.…”
Section: Introductionmentioning
confidence: 99%
“…Che et al demonstrated that during the final phase of particle drying in a spouted bed, intraparticle heat and mass diffusion primarily control the drying rate. They employed a coupled CFD and discrete element method (DEM) (CFD–DEM) to model the gas–solid interactions within a spouted bed.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results were given for fitting the axial sinusoidal distribution during expansion, where the values of adjusted R 2 ranged from 0.72 to 0.95. Che et al 15 introduced a novel CFD-DEM model for spouted bed drying that combines intraparticle heat and mass diffusion. It was shown that the CFD-DEM model effectively reproduced the reasonable heat and mass transfer laws of spouted-bed particle drying process characterized by an overall decrease in transfer rates.…”
mentioning
confidence: 99%